ASSESSMENT OF THREATS OF KEY ELEMENTS IN SUBSECTOR THE CRITICAL INFRASTRUCTURE OF WATER TRANSPORTATION IN THE SLOVAK REPUBLIC (Perner's Contacts, 2019)
Paper deals the inland waterway transport in the Slovak Republic, focusing on the key elements that can be partially or completely out of service due to the negative effects of natural elements. The authors assessed individual threats and, to the most serious, authors have suggested possible measures to reduce the risk of occurrence of an extraordinary event.
Keywords: infrastructure; road; transport; threats; vessel; harbour; elements; waterway